2019
DOI: 10.5089/9781484397015.001
|View full text |Cite
|
Sign up to set email alerts
|

Growth at Risk: Concept and Application in IMF Country Surveillance

Abstract: The growth-at-risk (GaR) framework links current macrofinancial conditions to the distribution of future growth. Its main strength is its ability to assess the entire distribution of future GDP growth (in contrast to point forecasts), quantify macrofinancial risks in terms of growth, and monitor the evolution of risks to economic activity over time. By using GaR analysis, policymakers can quantify the likelihood of risk scenarios, which would serve as a basis for preemptive action. This paper offers practical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Adrian et al (2018) have confirmed this result extending the sample to different countries and have pushed this view further by defining the concept of growth at risk as GDP growth at the lower fifth percentile of the GDP growth distribution, conditional on an index of financial stress. Building on this work, several recent papers have explored the idea, while policy institutions have adopted the methodology to monitor risk in different countries (see, for example, Prasad et al, 2019 for a description of the use of this method at the IMF). The appeal of this approach to policy work is that it provides a framework in which forecasting can be thought of as a risk managing exercise (see Kilian and Manganelli, 2008 for the first development of this idea).…”
Section: Introductionmentioning
confidence: 99%
“…Adrian et al (2018) have confirmed this result extending the sample to different countries and have pushed this view further by defining the concept of growth at risk as GDP growth at the lower fifth percentile of the GDP growth distribution, conditional on an index of financial stress. Building on this work, several recent papers have explored the idea, while policy institutions have adopted the methodology to monitor risk in different countries (see, for example, Prasad et al, 2019 for a description of the use of this method at the IMF). The appeal of this approach to policy work is that it provides a framework in which forecasting can be thought of as a risk managing exercise (see Kilian and Manganelli, 2008 for the first development of this idea).…”
Section: Introductionmentioning
confidence: 99%
“…A useful framework to link macrofinancial conditions and growth outlook is provided by the recent strand of Growth-at-Risk (GaR) literature. Empirical research developed by Giannone at the New York Federal Reserve Bank (2016, 2019) and its adaptations for IMF country surveillance (Prasad et al, 2019) provide a useful toolkit to look at the entire projected growth distribution and estimate the severity and likelihood of a recession given a set of country-specific macroeconomic and financial variables. This paper applies the GaR methodology to evaluate risks to GDP growth in the Dominican Republic, which offers three advantages.…”
Section: Figure 1 Developments In Real and Financial Sectorsmentioning
confidence: 99%
“…Indeed the 'Growth-at-Risk' framework of Adrian et al (2019) is already regularly published by several institutions to detect vulnerabilities of macroeconomic conditions; see e.g. Prasad et al (2019). 3 In a similar vein, Giglio et al (2016) examine the predictive power of several systemic risks measures for the distribution of industrial production growth and use these findings to obtain an aggregate index of risk.…”
Section: Introductionmentioning
confidence: 99%